Respuesta :

5naka

4x+2y=12

divide by 2

2x+y=6

y=6-2x

substitute to first equation

y=y

2x-2=6-2x

4x=8

x=2

y=2x-2=2(2)-2=2

hence the solution (x,y) is (2,2)

Answer:

(2,2)

Step-by-step explanation:

y=2x-2 and 4x+2y=12

Since the first equation is solved for y, we can substitute it into the second equation

4x +2(2x-2) =12

Then we distribute  the 2

4x+4x -4 =12

Combine like terms

8x-4 =12

Add 4 to each side

8x -4+4 =12 +4

8x = 16

Divide by 8

8x/8 = 16/8

x = 2

Now that we have x, we need to find y

y =2x-2

Substituting x=2

y =2(2)-2

y = 4-2

y=2

(2,2)